Oxidative stress and inflammation in diabetic nephropathy: role of polyphenols - Qi Jin; Tong‐Tong Liu; Yuan Qiao; Donghai Liu; Liping Yang; Huimin Mao; Fang Ma; Yuyang Wang; Liang Peng; Yongli Zhan (2023)
Diabetic nephropathy (DN) often leads to end-stage renal disease. Oxidative stress demonstrates a crucial act in the onset and progression of DN, which triggers various pathological processes while promoting the activation of inflammation and forming a vicious oxidative stress-inflammation cycle that induces podocyte injury, extracellular matrix accumulation, glomerulosclerosis, epithelial-mesenchymal transition, renal tubular atrophy, and proteinuria. Conventional treatments for DN have limited efficacy. Polyphenols, as antioxidants, are widely used in DN with multiple targets and fewer adverse effects. This review reveals the oxidative stress and oxidative stress-associated inflammation in DN that led to pathological damage to renal cells, including podocytes, endothelial cells, mesangial cells, and renal tubular epithelial cells. It demonstrates the potent antioxidant and anti-inflammatory properties by targeting Nrf2, SIRT1, HMGB1, NF-κB, and NLRP3 of polyphenols, including quercetin, resveratrol, curcumin, and phenolic acid. However, there remains a long way to a comprehensive understanding of molecular mechanisms and applications for the clinical therapy of polyphenols.